Do Long-Term Conservation Pasture Management Practices Influence Microbial Diversity and Antimicrobial Resistant Genes in Runoff? - Yang, Yichao; Ashworth, Amanda J.; Durso, Lisa M.; Savin, Mary; DeBruyn, Jennifer M.; Cook, Kimberly; Moore, Philip A.; Owens, Phillip R. (Frontiers in Microbiology, 2021)
Runoff from land-applied manure and poultry litter is one mechanism by which manure-borne bacteria are transported over large distances in the environment. There is a global concern that antimicrobial resistant (AMR) genes may be transmitted through the food chain from animal manures to soil to surface water. However, details are lacking on the ecology of AMR genes in water runoff, as well as how conservation management practices may affect the runoff microbiome or minimize the movement of AMR genes. The aim of this study was to identify microbial community structure and diversity in water runoff following 14-years of poultry litter and cattle manure deposition and evaluate the amount of AMR genes under five conventional and conservation pasture management strategies. Since 2004, all watersheds received annual poultry litter at a rate of 5.6 Mg ha−1 and were consistently managed. Surface runoff samples were collected from each watershed from 2018-2019, characterized using Illumina 16S rRNA gene amplicon sequencing and enumerated for four AMR-associated genes (ermB, sulI, intlI, and blactx-m-32) using quantitative PCR. Overall, long-term pasture management influenced water microbial community structure, with effects differing by year (P<0.05). Bacterial richness (Chao index) was influenced by pasture management, with lowest richness occurring in the control (nearby non-agricultural water source) and greatest under fields that were hayed (no cattle presence). Runoff bacterial richness in watersheds increased following poultry litter applications, indicating poultry litter is a possible source of bacteria and altered runoff community structure. The blactx-m-32 gene was not detected in any surface water sample. The remaining three AMR genes were absent in the non-agricultural control, but present in agricultural samples. However, there was no impact (P >0.05) from pasture management on the abundance of these genes, indicating both conventional and conservation practices have similar ecologies for these targets. Although there was a greater detection of sulI genes from runoff in continuously grazed systems in 2019, with hay being lowest in 2019. Results illustrate that conservation pasture management practices may influence bacterial richness in water runoff, but these changes in richness do not greatly impact target AMR genes in the U.S’ largest land-use category.